Implementation of Problem Based Learning Based on Caring Community in Mathematics Teaching Materials for Students of SMA Ibrahimy 2 Sukorejo - MOH. ATIKURRAHMAN (Program Studi Pendidikan Matematika, Fakultas Ilmu Pendidikan, Universitas Timor, 2025)
This study aims to examine the implementation of a Problem Based Learning (PBL) model integrated with Caring Community in mathematics teaching materials on vectors at SMA Ibrahimy 2 Sukorejo, addressing students’ persistent difficulties in mathematical problem-solving due to conventional approaches that neglect affective dimensions. Using a sequential explanatory mixed methods design, the study involved 30 students in the experimental class and 31 in the control class. Data were collected through learning achievement tests and observation, then analyzed quantitatively (normality test, homogeneity test, t-test, and normalized gain) and qualitatively (thematic analysis). Results show the experimental class’s mean post-test score (82.40) was significantly higher than the control class (68.50) (p = 0.000). Qualitative findings reveal that Caring Community fostered an empathetic, collaborative classroom climate that enhanced active participation and reduced math anxiety. The study concludes that the PBL Caring Community model effectively improves students’ mathematical abilities and aligns with the pesantren-based cultural context emphasizing solidarity and care.